The Role of English Courses in Logistics Management Study Program at Banyuwangi Marine Academy: Qualitative Research - Muhamad Alfi Khoiruman Alfi (Darussalam English Journal (DEJ), 2022)
English is the language used by some parts of the world community to communicate globally. English courses at the Banyuwangi Marine Academy, especially in the Logistics Management study program, are mandatory subjects that must be taken by students. English has an important role because it is widely used in meeting the requirements of both graduates and jobs. Good graduates in education are meant to produce graduates who are able to master English. Even so, there are many obstacles encountered in learning English courses, including: (1) Students' views of English courses. (2) lack of facilities and infrastructure in learning. (3) Insufficient material. (4) inadequate teaching staff or lecturers. This condition at least provides an answer regarding the geography education study program that has not been maximized. The problems found make the learning process not optimal so that the quality of education in the geography education study program is not optimal and graduates are unable to compete universally. As a result, graduates cannot compete with students who have non-vocational education. So it can be concluded that the English course has a very important role in the Logistics Management study program at the Banyuwangi Marine Academy.